The fallacies of Cold War deterrence and a new direction - Payne, Keith B. (University Press of Kentucky, 2001)
In 1938, Prime Minister Neville Chamberlain hoped that a policy of appeasement would satisfy Adolf Hitler's territorial appetite and structured British policy accordingly. This plan was a failure, chiefly because Hitler was not a statesman who would ultimately conform to familiar norms. Chamberlain's policy was doomed because he had greatly misjudged Hitler's basic beliefs and thus his behavior. U.S. Cold War nuclear deterrence policy was similarly based on the confident but questionable assumption that Soviet leaders would be rational by Washington's standards; they would behave reasonably wh.